Gods in the desert : religions of the ancient Near East - Holland, Glenn Stanfield, 1952- (Rowman & Littlefield Publishers, 2009)
Gods in the Desert explores the fascinating religious cultures of the ancient Near East. From the mysterious pyramids, tombs, and temples of Egypt to the powerful heroes, gods, and legends of Mesopotamia, Glenn Holland guides readers through the early religions that are the root of many of today's major faiths. Holland compares the religions of ancient Egypt, Mesopotamia, and Syria-Palestine, including Israel and Judah, from the Neolithic era through the conquest of Alexander the Great. He provides a historical survey of each region, then discusses the gods, the rulers, the afterlife, and th.